1999
DOI: 10.1017/s1446788700000884
|View full text |Cite
|
Sign up to set email alerts
|

Existence and uniqueness of a solution for a minimization problem with a generic increasing function

Abstract: In this paper we study the existence and uniqueness of a solution for minimization problems with generic increasing functions in an ordered Banach space X. The standard approaches are not suitable in such a setting. We propose a new type of perturbation adjusted for the problem under consideration, prove the existence and point out sufficient conditions providing the uniqueness of a solution. These results are proved by assuming that the space X enjoys the following property: each decreasing norm-bounded seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…When we say that a certain property holds for a generic element of a complete metric space Y we mean that the set of points which have this property contains a Gg everywhere dense subset of Y. Such an approach, when a certain property is investigated for the whole space Y and not just for a single point in Y, has already been successfully applied in many areas of Analysis [1,2,3,4,5,11,12,13]. The first generic result in monotonic analysis was obtained in [11] where we showed that a generic increasing function defined on an ordered Banach space has a point of minimum.…”
Section: Introductionmentioning
confidence: 99%
“…When we say that a certain property holds for a generic element of a complete metric space Y we mean that the set of points which have this property contains a Gg everywhere dense subset of Y. Such an approach, when a certain property is investigated for the whole space Y and not just for a single point in Y, has already been successfully applied in many areas of Analysis [1,2,3,4,5,11,12,13]. The first generic result in monotonic analysis was obtained in [11] where we showed that a generic increasing function defined on an ordered Banach space has a point of minimum.…”
Section: Introductionmentioning
confidence: 99%
“…The study of a generic existence of solutions in optimization has recently been a rapidly growing area of research (see [1,2,3,4,5,6,8,9,10,12,13,14,15] and the references mentioned there). Instead of considering the existence of solutions for a single cost function, we study it for a space of all such cost functions equipped with an appropriate complete uniformity and show that a solution exists for most of these functions.…”
Section: Introductionmentioning
confidence: 99%
“…The property (A) is well known in the theory of ordered Banach spaces (see, e.g., [7,10,11]). Recall that the cone X + has the property (A) if the space X is reflexive.…”
Section: Introductionmentioning
confidence: 99%